Clinical Reasoning in the Primary Care Setting: Two Scenario-Based Simulations for Residents and Attendings - Alexis Battista; Abigail Konopasky; Divya Ramani; Megan Ohmer; Jeffrey Mikita; Anna Howle; Sarah Krajnik; Dario Torre; Steven J. Durning (Association of American Medical Colleges, 2018)
Introduction We describe the development and implementation of tools medical educators or researchers can use for developing or analyzing residents' through attending physicians' clinical reasoning in an outpatient clinic setting. The resource includes two scenario-based simulations (i.e., diabetes, angina), implementation support materials, an open-ended postencounter form, and a think-aloud reflection protocol. Method We designed two scenarios with potential case ambiguity and contextual factors to add complexity for studying clinical reasoning. The scenarios are designed to be used prior to an open-ended written exercise and a think-aloud reflection to elicit reasoning and reflection. We report on their implementation in a research context but developed them to be used in both educational and research settings. Results Twelve physicians (five interns, three residents, and four attendings) considered between three and six differential diagnoses (M = 4.0) for the diabetes scenario and between three and nine differentials (M = 4.3) for angina. In think-aloud reflections, participants reconsidered their thinking between zero and 14 times (M = 3.5) for diabetes and zero and 11 times (M = 3.3) for angina. Cognitive load scores ranged from 4 to 8 (out of 10; M = 6.2) for diabetes and 5 to 8 (M = 6.6) for angina. Participants rated scenario authenticity between 4 and 5 (out of 5). Discussion The potential case content ambiguity, along with the contextual factors (e.g., patient suggesting alternative diagnoses), provides a complex environment in which to explore or teach clinical reasoning.